Cardiorenal function and survival in in-hospital cardiac arrest: A nationwide study of 22, 819 cases. (March 2022) - Berglund, Sara; Andreasson, Axel; Rawshani, Aidin; Hirlekar, Geir; Lundgren, Peter; Angerås, Oscar; Mandalenakis, Zacharias; Redfors, Björn; Holm, Astrid; Hagberg, Eva; Ricksten, Sven-Erik; Friberg, Hans; et al.
Graphical abstract: Abstract: Background: We studied the association between cardiorenal function and survival, neurological outcome and trends in survival after in-hospital cardiac arrest (IHCA). Methods: We included cases aged ≥ 18 years in the Swedish Cardiopulmonary Resuscitation Registry during 2008 to 2020. The CKD-EPI equation was used to calculate estimated glomerular filtration rate (eGFR). A history of heart failure was defined according to contemporary guideline criteria. Logistic regression was used to study survival. Neurological outcome was assessed using cerebral performance category (CPC). Results: We studied 22, 819 patients with IHCA. The 30-day survival was 19.3%, 16.6%, 22.5%, 28.8%, 39.3%, 44.8% and 38.4% in cases with eGFR < 15, 15–29, 30–44, 45–59, 60–89, 90–130 and 130–150 ml/min/1.73 m 2, respectively. All eGFR levels below and above 90 ml/min/1.73 m 2 were associated with increased mortality. Probability of survival at 30 days was 62% lower in cases with eGFR < 15 ml/min/1.73 m 2, compared with normal kidney function. At every level of eGFR, presence of heart failure increased mortality markedly; patients without heart failure displayed higher mortality only at eGFR below 30 ml/min/1.73 m 2 . Among survivors with eGFR < 15 ml/min/1.73 m 2, good neurological outcome was noted in 87.2%. Survival increased in most groups over time, but most for those with eGFR < 15 ml/min/1.73 m 2, and least for those with normal eGFR. Conclusions: All eGFR levels below and above normal range are associated with increased mortality and this association is modified by the presence of heart failure. Neurological outcome is good in the majority of cases, across kidney function levels and survival is increasing.